PENGARUH INOVASI PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC YAMAHA MIO M3 125 BLUECORE (STUDI DI DEALER YAMAHA SURABAYA SELATAN) - MAHARANI, APRILIA (Jurnal Ilmu Manajemen (JIM), 2017)
The current business development is colored by various kinds of competition. Seeing these conditions cause business people increasingly required to have the right strategy in meeting sales targets. Yamaha make new innovations on Mio Bluecore Mio is a fuel efficient that is expected to increase sales. With this bluecore technology Mio was once impressed as a motor with wasteful fuel to be more efficient, which will impact on purchasing decisions .This study aims to analyze and discuss the effect of product innovation and brand image on the purchase decision mio m3 125 Bluecore .This research was conducted at south Surabaya dealer use such data with 210 respondents. Sampling method in use right is judgmental sampling. Instrument used for data collection in research was that have been analyzed using such likert scale. Statistical analysis used is multiple linear regression. The results showed that the variable of product innovation had positive and significant effect to decision of mio m3 125 Bluecore. Brand image variables have positive and significant influence to decision of mio m3 125 Bluecore. Keywords: product innovation, brand image, purchase decision.